Training and Assistance for Writing of the Accreditation form of SD Impres Negeri Lima of Central Maluku - Laila Sahubauwa; Nana Ronawan Rambe; Abajaidun Mahulauw; Corneli Pary (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
This PKM (Community Service) activity is the form of training and mentoring which aims to provide material provisions for teachers related to preparation for accreditation. The next step is to complete the files for proposing an accreditation form and the last one is an online trial of accreditation training/simulation. This community service activity is carried out by applying the lectures, demonstration, and interactive discussion methods. Based on the activities that have been carried out. The results of the training and mentoring obtained are: 1) the teachers get the provision of information related to Accreditation, 2) the teachers have completed the application form files, and 3) the teachers are able to carry out the simulation stages which are given online.Keywords. Training, Assistance, Accreditation